2013
DOI: 10.1002/oby.20039
|View full text |Cite
|
Sign up to set email alerts
|

A dairy‐based high calcium diet improves glucose homeostasis and reduces steatosis in the context of preexisting obesity

Abstract: Objective: High dietary calcium (Ca) in the context of a dairy food matrix has been shown to reduce obesity development and associated inflammation in diet-induced obese (DIO) rodents. The influence of Ca and dairy on these phenotypes in the context of preexisting obesity is not known. Furthermore, interpretations have been confounded historically by differences in body weight gain among DIO animals fed dairy-based protein or high Ca. Design and Methods: Adiposity along with associated metabolic and inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Meanwhile, our results showed that calcium supplementation significantly reduced blood glucose and serum insulin levels, and improved glucose tolerance and insulin sensitivity in HFD-fed mice. Similarly, the beneficial effects of dietary calcium on glycemic control has been indicated in many studies [16,18,38]. However, consumption of high calcium provided no effect on glycemic control in overweight patients with type 2 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, our results showed that calcium supplementation significantly reduced blood glucose and serum insulin levels, and improved glucose tolerance and insulin sensitivity in HFD-fed mice. Similarly, the beneficial effects of dietary calcium on glycemic control has been indicated in many studies [16,18,38]. However, consumption of high calcium provided no effect on glycemic control in overweight patients with type 2 diabetes [17].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, calcium also plays an important role in regulating glucose uptake in the isolated working rat heart [13], mice skeletal muscle [14], and 3T3-L1 cells [15]. Moreover, dietary calcium has been confirmed to elicit beneficial effects on body weight/fat reduction and glycemic control [16][17][18]. Although the increase of fat oxidation and fecal fat excretion [19], the elevation of adipose tissue apoptosis [20], and the gut microbiota [16,21] have been implicated to be partly involved, the mechanisms by which calcium modulates body weight/fat and glucose homeostasis are still not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…In other study, low dietary consumption of fiber positively associated with the pathogenesis of non-alcoholic fatty liver disease (Papandreou et al, 2012). Lower fiber consumption may also be associated with higher BMI, higher levels of serum lipids and lipid accumulation (Thomas et al, 2013).…”
Section: Discussionmentioning
confidence: 78%
“…However, anti-inflammatory actions of calcitriol have also been reported in humans [15], and serum calcitriol has been reported to be significantly lower in obese verses non-obese human subjects [16]. In diet-induced obese (DIO) mice fed high calcium or high-calcium plus dairy, circulating calcitriol did not correlate with alterations in systemic or WAT inflammation [17,18]. Thus, changes in calcitriol due to dietary calcium cannot fully explain the apparent anti-inflammatory effects of dairy.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models of obesity, inclusion of dairy or dairy-based proteins in the diet reduces weight gain and adiposity, even in the absence of lower energy intake. In some studies in DIO mice fed a high fat diet containing a dairy matrix (e.g., a calcium rich, non-fat dry milk (NFDM) protein and carbohydrate-based diet), energy intake was modestly increased, resulting in lower feed efficiency [17,18]. The etiology of these effects on food intake and energy balance remains to be ascertained.…”
Section: Introductionmentioning
confidence: 99%